Evaluation of the efficiency of advanced tools for organizational training of concentrated construction - Tugai, A.; Horbach, M.; Malikhin, M.; Sobol, D.; Degtyarova, I. (Ways to Improve Construction Efficiency, 2022)
The article researched and established that in order to improve the tools, models and methods of organizational-technological and geo-informational modeling of complex organizational training, the branch specifics of objects were taken into account, since cluster construction represents a variety of objects, and is also characterized by significant uncertainty of information support . At the same time, a significant amount of geoinformation, which is necessary for high-quality organizational and technological preparation of the territories allocated for construction, is not used. The work analyzes the main tasks and stages of complex organizational preparation of concentrated construction, existing technologies of automation of construction processes, to identify the technology of geoinformation modeling taking into account the specifics of the industry and the necessary tools for assessing the adequacy of the necessary information support. The article describes the practical implementation of a geoinformation modeling tool for complex organizational preparation of concentrated construction for the development of a digital geoinformation 3D model of a consolidated plan of engineering networks based on the modern GEOCAD software complex of the GEOKAD company - a domestic developer of engineering GIS, which works in the AutoCAD 3D modeling environment. The researched experimental approbation of the methodology for assessing the reliability of the organizational preparation of the territorial cluster was carried out on the example of the development of the territorial cluster in the city of Vinnytsia, taking into account the possible states of the system and with the calculation of reliability indicators of consolidated calendar plans for the preparation of construction sites for the cluster objects. An analysis of the geoinformation provision of all cycles of organizational training was carried out and showed that in real practice there is no single system and comprehensive approach to both the formation of information provision and the functioning of the services of the customer-builder. In this connection, models of the functioning of the complex training system were considered and improved.